Sly the Sleuth and the pet mysteries - Napoli, Donna Jo, 1948- (Dial Books for Young Readers, 2005)
Sly the Sleuth, also known as Sylvia, solves three mysteries for her friends and neighbors, all involving pets, through her detective agency, Sleuth for Hire.